Three-dimensional characterization of bonding features for asphalt pavement interface using a novel interlayer isolation film. (13th December 2021) - Huang, Hengwei; Zhan, You; Tao, Yale; Ai, Changfa; Ren, Dongya; Jin, Dayong
Graphical abstract: Highlights: Layered pavement structure was separated by a novel interlayer isolation film. Characterizing the interface bonding features between asphalt concrete layers. Correlating the damage rate of the film to interface bonding parameters. Abstract: Pavement interface bonding largely depends on the interface topography characteristics. This study presents a procedure to characterize the interface bonding features between different types of asphalt concrete layers and reveals the difference of the "interaction effect" between layers. The top and bottom layers of asphalt mixtures were non-destructively separated by a novel interlayer isolation film. An ultra-high-resolution three-dimensional (3D) laser scanner was used to acquire 3D interface data of interlayer. Analysis of variance (ANOVA) was performed to examine the relationship between the damage rate of the interlayer isolation film and its corresponding bonding characteristics. The binary analysis results showed that the damage rate of the isolation film was different due to the asphalt mixture with different gradations in the top and bottom layers. The arithmetic mean curvature ( Spc ), height distribution skewness ( Ssk ), and root mean square deviation ( Sq ) have the most significant effects on the isolation film damage rate at the 99.9 % confidence interval. These characteristics can be used to describe pavement interlayer bonding states. This study provides theoretical support for optimizing the bonding characterization of pavement interfaces.